Case report: Motor neuron disease phenotype associated with symptomatic copper deficiency: Challenging diagnosis and treatment - Benkirane, Adam; Warlop, Thibault; Ivanoiu, Adrian; Baret, Pierre; Wiame, Elsa; Haufroid, Vincent; Duprez, Thierry; Hantson, Philippe (Frontiers in Neurology, 2023)
Copper deficiency is an acquired condition that can lead to neurologic dysfunctions, such as myelopathy, motor neuron impairment, polyneuropathy, cognitive impairment and optic nerve neuropathy. Associated biological findings are low serum copper and ceruloplasmin levels, with low copper urinary excretion. We report the case of a previously healthy 59-year-old man who presented a complex neurological picture starting with symptoms and radiological signs consistent with a degenerative myelopathy in the presence of persisting low serum copper and ceruloplasmin despite oral and intravenous copper supplementation. Over the time, his symptoms evolved to a motor neuron disease mimicking amyotrophic lateral sclerosis (ALS). The potential role of copper deficiency is discussed, together with the difficulties of the biomonitoring of copper supplementation.